Geometry of quantum states : an introduction to quantum entanglement - Bengtsson, Ingemar, 1967- (Cambridge University Press, 2006)
An introduction to the key concepts of quantum information processing. The authors cover basic quantum theory, the geometry of quantum state spaces and quantum entanglement, which has become a key resource for quantum computation. This richly-illustrated book is useful to graduates and researchers interested in quantum information theory.